Multispecies Analysis of Expression Pattern Diversification in the Recently Expanded Insect Ly6 Gene Family - Tanaka, Kohtaro (2017)
The deposited article version is a "MBE Advance Access" published on March 4, 2015" provided by Oxford University Press, and it contains attached the supplementary materials within the pdf.